Asian corporate bond index. - Tan, Kelvin Chung Wai. (2008)
The project aims to form an index solely for corporate bonds in emerging Asian bond markets. The focus of Asian securities markets has always been on the equity market, one of the reasons being the lack of a benchmark. It is hoped that with the formation of this index, investors will look to bonds as an alternative to financing and investments in Asia, with the index providing a basis with which to gauge the performance of the fixed-income instruments.